A Report of the Efforts of the Veterans Health Administration National Antimicrobial Stewardship Initiative. (25th January 2017) - Kelly, Allison A.; Jones, Makoto M.; Echevarria, Kelly L.; Kralovic, Stephen M.; Samore, Matthew H.; Goetz, Matthew B.; Madaras-Kelly, Karl J.; Simbartl, Loretta A.; Morreale, Anthony P.; Neuhauser, Melinda M.; Roselle, Gary A.
Abstract : OBJECTIVE: To detail the activities of the Veterans Health Administration (VHA) Antimicrobial Stewardship Initiative and evaluate outcomes of the program. DESIGN: Observational analysis. SETTING: The VHA is a large integrated healthcare system serving approximately 6 million individuals annually at more than 140 medical facilities. METHODS: Utilization of nationally developed resources, proportional distribution of antibiotics, changes in stewardship practices and patient safety measures were reported. In addition, inpatient antimicrobial use was evaluated before and after implementation of national stewardship activities. RESULTS: Nationally developed stewardship resources were well utilized, and many stewardship practices significantly increased, including development of written stewardship policies at 92% of facilities by 2015 ( P <.05). While the proportional distribution of antibiotics did not change, inpatient antibiotic use significantly decreased after VHA Antimicrobial Stewardship Initiative activities began ( P <.0001). A 12% decrease in antibiotic use was noted overall. The VHA has also noted significantly declining use of antimicrobials prescribed for resistant Gram-negative organisms, including carbapenems, as well as declining hospital readmission and mortality rates. Concurrently, the VHA reported decreasing rates of Clostridium difficile infection. CONCLUSIONS: The VHA National Antimicrobial Stewardship Initiative includes continuing education, disease-specific guidelines, and development of example policies in addition to other highly utilized resources. While no specific ideal level of antimicrobial utilization has been established, the VHA has shown that improving antimicrobial usage in a large healthcare system may be achieved through national guidance and resources with local implementation of antimicrobial stewardship programs. Infect Control Hosp Epidemiol 2017;38:513–520